SDSS-IV MaNGA: identification of active galactic nuclei in optical integral field unit surveys. Issue 2 (26th October 2017) - Wylezalek, Dominika; Zakamska, Nadia L.; Greene, Jenny E.; Riffel, Rogemar A.; Drory, Niv; Andrews, Brett H.; Merloni, Andrea; Thomas, Daniel
Abstract: In this paper, we investigate 2727 galaxies observed by MaNGA as of 2016 June to develop spatially resolved techniques for identifying signatures of active galactic nuclei (AGNs). We identify 303 AGN candidates. The additional spatial dimension imposes challenges in identifying AGNs due to contamination from diffuse ionized gas, extraplanar gas and photoionization by hot stars. We show that the combination of spatially resolved line diagnostic diagrams and additional cuts on H α surface brightness and H α equivalent width can distinguish between AGN-like signatures and high-metallicity galaxies with low-ionization nuclear emission-line regions-like spectra. Low-mass galaxies with high specific star formation rates are particularly difficult to diagnose and routinely show diagnostic line ratios outside of the standard star formation locus. We develop a new diagnostic – the distance from the standard diagnostic line in the line-ratio space – to evaluate the significance of the deviation from the star formation locus. We find 173 galaxies that would not have been selected as AGN candidates based on single-fibre spectral measurements but exhibit photoionization signatures suggestive of AGN activity in the Mapping Nearby Galaxies at APO resolved observations, underscoring the power of large integral field unit surveys. A complete census of these new AGN candidates is necessary to understand their nature and probe the complex co-evolution of supermassive black holes and their hosts.